The Role of Mental Concentration on Accuracy of Upper Passing in Volleyball: A Systematic Literature Review - Hanafi, Suriah (Journal Physical Health Recreation (JPHR), 2025)
This study aims to systematically examine the role of mental concentration on the accuracy of the upper pass technique in volleyball. The method used is the Systematic Literature Review (SLR) by analyzing eight relevant scientific articles using experimental, correlational, and quantitative descriptive approaches. The results of the analysis show that mental concentration plays a significant role in improving the accuracy of the upper pass. Strategies such as mental imagery, positive self-talk, external focus of attention, mental relaxation, and mindfulness training have been proven effective in supporting upper pass performance. This study confirms that mental concentration not only contributes to technical aspects but also forms mental resilience in facing the pressure of the game. Therefore, it is important for coaches and physical educators to integrate mental training into the volleyball training curriculum in order to optimize the overall performance of students.